How are we actually doing? Comparing water and sanitation in Kenya with MDG and SDG criteria - Lauren Trepanier (IWA Publishing, 2021)
This cross-sectional study assesses the extent to which water and sanitation access differs among respondents in three counties in Western and Rift Valley Kenya. By using both Millennium Development Goal (MDG) and Sustainable Development Goal (SDG) criteria, we utilize important geographical nuances of SDG water and sanitation provisioning across rural and urban settings to highlight the strengths and weaknesses of the MDGs and SDGs in each context. Purposive heterogenous sampling using local knowledge was employed to select households who represent varying rural and urban contexts with differing land use practices. Differences in water and sanitation access based on varying MDG/SDG water criteria showcase how the shift from technology-based criteria to service provisioning criteria affects understanding of progress and remaining challenges toward water and sanitation provisioning. Results indicate that although 72% of respondents have Improved Water per MDG criteria, only 34% have Safely Managed Water and 36% have Basic Water as per the SDGs. Component analyses show SDG criteria with the lowest percentages of achievement were: microbial and fluoride water quality and that sanitation facilities were not shared with other households. These results pinpoint areas where there is a need for increased research and investment surrounding how to achieve specific SDG criteria and increase access to safe water and sanitation. Highlights SDG water service provisioning is lower than MDG Improved Water access.; Safely Managed Water and Sanitation criteria with lowest percentages of achievement are fluoride and microbial water quality and sanitation facilities, which are not shared.; Component analyses show which SDG criteria may limit realization of water and sanitation provisioning.; SDG criteria have stronger linkages between WASH provisioning and rural and urban settings.;